The contributions of convergent thinking, divergent thinking, and schizotypy to solving insight and non-insight problems. (3rd July 2017) - Webb, Margaret E.; Little, Daniel R.; Cropper, Simon J.; Roze, Kayla
ABSTRACT: The ability to generate diverse ideas (divergent thinking) is valuable in solving creative problems (e.g., insight problems); yet, however advantageous, this ability is insufficient to solve the problem alone and requires the ability to logically deduce an assessment of correctness of each solution (convergent thinking). Positive schizotypy may help isolate the aspects of divergent thinking prevalent in insight problem solving. Participants were presented with a measure of schizotypy (Oxford-Liverpool Inventory of Feelings and Experiences), divergent and convergent thinking tasks, insight problems, and non-insight problems. We found no evidence for a relationship between schizotypy and insight problem solving. Relationships between divergent thinking and insight problem solving were also surprisingly weak; however, measures of convergent thinking had a stronger relationship with problem solving. These results suggest that convergent thinking is more important than divergent thinking in problem solving.